Persepsi Gaya Mengajar Guru dan Prestasi Belajar Matematika Pada Murid SD di Jakarta - Sonna Etika; Agoes Dariyo; Roswiyani P. Zahra (Journal An-Nafs: Kajian Penelitian Psikologi, 2017)
Sutanto (2008) found that the mathematic learning achievement of Augustinus High School Students in Kediri was also influenced by their perception about their teacher’s teaching style. In a study-case to the students of SMPN 19 in Jambi, Sumadi (2010) found that the perception of those Junior High School students about their teacher’s teaching style contributed the effect to their mathematic learning achievement. Based on the past studies, researcher interested to find out a relationship between the perception of teacher’s teaching style and mathematic learning achievement on elementary school students. The participants of this research are 424 fifth-grade elementary school students in West Jakarta. This research result suggest that there is no relationship between the perception of teacher’s teaching style and mathematic learning achievement on elementary school students